2020
DOI: 10.1027/1864-9335/a000413
|View full text |Cite
|
Sign up to set email alerts
|

When Does Imagined Contact Reduce Prejudice?

Abstract: Abstract. Imagined contact has been argued to reduce prejudice. Although extant research supports this argument, replication attempts have been unsuccessful. To resolve conflicting evidence from previous studies, this study examined the effect of imagined contact on explicit and implicit prejudice against Kurds and Syrians in Turkey. Using data from 335 Turkish undergraduate students, the moderating role of ethnic and national identification in the imagined contact effect was tested. Results indicated that ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…However, perceived realism of the scenarios functioned as an important covariate and warrants greater attention, especially when considering the ecological validity of the findings. A further study, however, did not replicate our imagined contact findings in relation to Turks' attitudes toward Kurds and Syrians; Firat and Ataca (2020) demonstrated that a standard imagined contact scenario did not improve explicit or implicit attitudes towards either group. These inconsistencies can be explained by a variety of mechanisms, such as differences in terms of manipulation instructions and settings involved in the scenarios, and the ethnic composition of the setting (East or West of Turkey).…”
Section: Intergroup Level Outcomescontrasting
confidence: 91%
See 1 more Smart Citation
“…However, perceived realism of the scenarios functioned as an important covariate and warrants greater attention, especially when considering the ecological validity of the findings. A further study, however, did not replicate our imagined contact findings in relation to Turks' attitudes toward Kurds and Syrians; Firat and Ataca (2020) demonstrated that a standard imagined contact scenario did not improve explicit or implicit attitudes towards either group. These inconsistencies can be explained by a variety of mechanisms, such as differences in terms of manipulation instructions and settings involved in the scenarios, and the ethnic composition of the setting (East or West of Turkey).…”
Section: Intergroup Level Outcomescontrasting
confidence: 91%
“…For example, contact with Armenians, another conflicted outgroup for Turks, is reported to be less frequent than contact with Kurds (Bağcı & Çelebi, 2017). Also, unlike Turkish-Kurdish relations, the relations between Turkish natives and Syrian refugees involve low levels of intergroup contact, and low intergroup conflict (Firat & Ataca, 2020).…”
Section: The Turkish-kurdish Intergroup Contextmentioning
confidence: 99%
“…In neutral or tourism environments, we found no significant differences between friendship potential and standard IIC, or between standard IIC and no IIC. Some research demonstrates that standard imagined contact is ineffective when compared to no IIC situations (e.g., Firat & Ataca, 2020; Lai et al, 2014). Because Türkiye has several ethnic communities (Andrews, 1992), the majority of members are likely to have frequent interethnic contacts in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Which, in line with Allport's (1954) original considerations, leads to reduced stigmatisation towards the portrayed minority group (mothers with a disability). However, these effects deserve further investigation, since the impact of non-real contacts on attitude changes is currently questioned by some scholars (Firat & Ataca, 2020).…”
Section: Discussionmentioning
confidence: 99%